Parents Communication Patterns to The Development of Children's Personality - Erlynda Ayu Kusumawati; Ega Listianingsih; Ratna Hidayah (Universitas Sebelas Maret, 2019)
Association of children in the era of technological development now is very free. For that, parents need to implement good communication patterns in children. The purpose of the articles of this is to determine the importance of a relationship as well as the implications for the pattern of communication the parents in the development of the personality of the child. The method of research that is used is qualitative methods using data collection techniques from library studies. The results of the article are discussed, namely, o rang parents in educating children should do approach to communication is based on the life of psychic children, because every child each has nature and character are different. Based on the discussion about the patterns of communication in the formation of the personality of the child can be concluded that the parents have a role large for the establishment and development of the personality of the child.